Creatine supplementation does not improve repeat sprint performance in soccer players - Smart, N. A.; McKenzie, S. G.; Nix, L. M.; Baldwin, S. E.; Page, K.; Wade, D.; Hampson, P. K. (Medicine & Science in Sports & Exercise, 1998)
National level soccer players (N = 11) were assigned to either a placebo or a creatine supplementation group. Creatine (24 gm) was supplemented with glucose. The study lasted six days. The creatine group increased by 1.9 kg in weight during the brief study time whereas the control group did not change. There were no effects of creatine supplementation on sprint performance in these highly skilled athletes. Implication. A brief exposure to creatine supplementation does not improve sprint performance in soccer players. It is possible that the higher the quality of the athlete, the less is the potential for creatine to affect performance.